An onset advantage without a preview benefit: neuropsychological evidence separating onset and preview effects in search. - Humphreys, G; Olivers, C; Yoon, E (2006)
Visual search is facilitated if half the distractors are presented as a preview prior to the presentation of the target and second set of distractors--the preview benefit [Watson, D. G., and Humphreys, G. W. Visual marking: Prioritizing selection for new objects by top-down attentional inhibition of old objects. Psychological Review, 104, 90-122, 1997]. On one account, the preview advantage is due to automatic capture of attention by the onsets in the second, search display [Donk, M., and Theeuwes, J. Visual marking beside the mark: Prioritizing selection by abrupt onsets. Perception and Psychophysics, 93, 891-900, 2001]. We provide a neuropsychological test of this assertion. We examined onset capture and preview benefits in search in a group of neuropsychological patients with unilateral parietal damage. We demonstrate a normal pattern of performance when patients detected targets defined by onsets relative to those defined by offsets, irrespective of whether the onset target fell contra- or ipsilateral to the lesion. In contrast, there was a normal preview benefit in search only for ipsilesional targets, and preview search was impaired in the contralesional field. The data demonstrate that the preview benefit can dissociate from the onset advantage in search, and that onsets remain strongly weighted for attention even in the contralesional field of patients with parietal lesions.